PENGARUH DISPLAY PRODUK PADA KEPUTUSAN PEMBELIAN KONSUMEN - Melati, Ina (Binus Business Review, 2012)
Most of ritel outlet recently using product display as a one of their best marketing strategy, the reason is quiet easy to be understood, since consumers are too easy to be teased by those kind of beautiful product display that is being displayed by the retail outlet. The good retail outlets are trying their best to design and make the very good product display, so they can attract more consumers and make them not thinking twice to visit their store and purchase lots of thing. Clearly seeing that an attractive product design is able to influence a consumer to make a buying decision.Â